Association analysis for detecting significant single nucleotide polymorphisms for phosphorus-deficiency tolerance at the seedling stage in soybean [Glycine max (L) Merr - Ning, Lihua (Breeding science, 2016)
Tolerance to low-phosphorus soil is a desirable trait in soybean cultivars. Previous quantitative trait locus (QTL) studies for phosphorus-deficiency tolerance were mainly derived from bi-parental segregating populations and few reports from natural population. The objective of this study was to detect QTLs that regulate phosphorus-deficiency tolerance in soybean using association mapping approach. Phosphorus-deficiency tolerance was evaluated according to five traits (plant shoot height, shoot dry weight, phosphorus concentration, phosphorus acquisition efficiency and use efficiency) comprising a conditional phenotype at the seedling stage. Association mapping of the conditional phenotype detected 19 SNPs including 13 SNPs that were significantly associated with the five traits across two years. A novel cluster of SNPs, including three SNPs that consistently showed significant effects over two years, that associated with more than one trait was detected on chromosome 3. All favorable alleles, which were determined based on the mean of conditional phenotypic values of each trait over the two years, could be pyramided into one cultivar through parental cross combination. The best three cross combinations were predicted with the aim of simultaneously improving phosphorus acquisition efficiency and use efficiency. These results will provide a thorough understanding of the genetic basis of phosphorus deficiency tolerance in soybean